Automatic system for electron tomography data collection in the ultra-high voltage electron microscope. (December 2017) - Cao, Meng; Nishi, Ryuji; Wang, Fang
Highlights: An automatic system for collection of tilt series for electron tomography based on the ultra-HVEM in Osaka University was developed. This system track the field of view and do focus in each tilt angle. The developed system can full automatically collect the tilt series with smaller time consumption. A toolkit based on image stitching is developed to expand the filed of view. A system with automatic tracking the filed of view and auto-focus was developed for collection of tilt series in electron tomography. Abstract: In this study, we report an automatic system for collection of tilt series for electron tomography based on the ultra-HVEM in Osaka University. By remotely controlling the microscope and reading the observation image, the system can track the field of view and do focus in each tilt angle. The automatic tracking is carried out with an image matching technique based on normalized correlation coefficient. Auto focus is realized by the optimization of image sharpness. A toolkit that can expand the field of view with technique of image stitching is also developed. The system can automatically collect the tilt series with much smaller time consumption.